PENGARUH KEPUASAN PELANGGAN, KUALITAS PRODUK, DAN EXPERIENTIAL MARKETING TERHADAP WORD OF MOUTH PADA PERCETAKAN SABILUL HAQ - MISMIWATI, MISMIWATI MISMIWATI (Islamic Economics Program, Faculty of Islamic Economics and Business, 2016)
This research using three independent variables that are customer satisfaction, product quality and experiential marketing while variable dependent is word of mouth. The purpose of this research is to analyze the influence of customer satisfaction, product quality, and experiential marketing to word of mouth in Sabilul HAQ printing. Research sampling is all the customer Sabilul HAQ printing. Based on that there are 88 respondents. Sampling technique using boring sampling. Data analysis method using quantitative analysis that are reliability test and validity test, classic assumption test, T test, F test, determination coefficient , and multiple linear regression analysis. The result show that customer satisfaction, product quality, experiential marketing variables has positive influence to word of mouth.Key word: customer satisfaction, product quality, experiential marketing , word of mouth